2010
DOI: 10.1097/mlr.0b013e3181d567bd
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adherence to Antihypertensive Agents on Clinical Outcomes and Hospitalization Costs

Abstract: Low adherence to AH agents is correlated with a higher risk of vascular events, hospitalization, and greater healthcare costs. An increased level of adherence to AH agents should provide a better health status for individuals and a net economic gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 34 publications
1
137
1
10
Order By: Relevance
“…The duration of abiraterone treatment in our study, which was slightly shorter in the postchemotherapy group than in the exception patient group, supports this notion. The median survival in our postchemotherapy group (12.0 [95% CI 11.0-19.0] mo) was slightly less than that observed in the COU-AA-301 trial 3 .0] mo), whereas the latter is similar to the survival in our exception patient group (14.0 [95% CI [11][12][13][14][15][16][17][18][19][20] mo). However, our patients were older than those in the COU-AA-301 trial , and the trial patients may have had a different comorbidity or disease profile, which we were unable to assess.…”
Section: Discussionmentioning
confidence: 61%
“…The duration of abiraterone treatment in our study, which was slightly shorter in the postchemotherapy group than in the exception patient group, supports this notion. The median survival in our postchemotherapy group (12.0 [95% CI 11.0-19.0] mo) was slightly less than that observed in the COU-AA-301 trial 3 .0] mo), whereas the latter is similar to the survival in our exception patient group (14.0 [95% CI [11][12][13][14][15][16][17][18][19][20] mo). However, our patients were older than those in the COU-AA-301 trial , and the trial patients may have had a different comorbidity or disease profile, which we were unable to assess.…”
Section: Discussionmentioning
confidence: 61%
“…Even modest nonadherence (e.g., 10-20 %) has been linked with clinically significant deteriorations in health outcomes, such as glycemic control, low-density lipoprotein cholesterol levels, and risk for coronary disease [21,22], as well as failure to achieve health improvements [23], leading to higher healthcare costs [21,24].…”
Section: Defining Medication Adherence Behaviormentioning
confidence: 99%
“…30 Reinforcing measures aimed at improving adherence to treatment is cost effective. 31,32 It has been suggested that the prescription to the whole population older than 55 years of age of a single pill containing a combination of CV drugs (the polypill) could prevent as much as 80% of CVD events 33 and be cost effective. 34 Part of the cost-effectiveness of the polypill is due to improvement in adherence to treatment, but which combination of drugs is most cost effective in which target population remains to be assessed.…”
Section: Cost-effectiveness Of Preventionmentioning
confidence: 99%